Aortic Aneurysm Eroding into the Spine - Rajab, T. Konrad; Beyene, Miriam W.; Yazdchi, Farhang; Menard, Matthew T. (AORTA, 2018)
Aortic aneurysms are usually asymptomatic until catastrophic rupture occurs. Ruptured abdominal aortic aneurysms classically present with acute back pain, shock, and a pulsatile abdominal mass. The natural history of some aortic aneurysms also includes a stage of contained rupture. This occurs when extravasation of blood from the ruptured aneurysm is contained by surrounding tissues. Here, the authors report the case of a chronic contained abdominal aortic aneurysm rupture that resulted in erosion of the spine.
Keywords: aortic aneurysm; rupture; contained rupture; surgery